The Effect of Income Taxes on Household Income - Auten, Gerald; Carroll, Robert (The Review of Economics and Statistics, 1999)
Research on the distribution of income during the 1980s has identified a trend towards increasing inequality, which may be the continuation and acceleration of trends spanning several decades. This paper explores to what extent behavioral responses to the tax changes during the 1980s may also explain the rising inequality. The 1986 Tax Reform Act is used as a natural experiment to explore the roles played by both taxes and a variety of nontax factors. Our principal finding is that both tax rates and nontax factors appear to have had significant effects on relative income growth during the late 1980s.